Inequalities in the psychological well-being of employed, single and partnered mothers: the role of psychosocial work quality and work-family conflict - Muhajarine Nazeem; Janzen Bonnie L; Dziak Ewelina (BMC, 2010)
Abstract Background A large body of international research reveals that single mothers experience poorer mental health than their partnered counterparts, with socioeconomic disadvantage identified as an important contributory factor in understanding this health disparity. Much less research, however, has focused specifically on the psychological well-being of single mothers who are employed, despite their growing presence in the labor force. Of the research which has considered employment, the focus has been on employment status per se rather than on other important work-related factors which may impact psychological health, such as psychosocial work quality and work-family conflict. The aim of this study was to: (1) compare employed single mothers and employed partnered mothers on measures of psychological distress, psychosocial work quality and work-family conflict; and (2) explore the potential role of work-family conflict and psychosocial work quality as explanations for any observed differences in psychological distress based on partner status. Method Analysis of data obtained from a cross-sectional telephone survey of employed parents in a mid-sized Western Canadian city. Analyses were based on 674 employed mothers (438 partnered and 236 single), who were 25-50 years old, with at least one child in the household. Results Compared to employed single mothers, employed partnered mothers were older, had more education and reported fewer hours of paid work. Single mothers reported higher levels of psychological distress, financial hardship, work-family conflict and poor psychosocial work quality. Statistical adjustment for income adequacy, psychosocial work quality and work-family conflict each independently resulted in single motherhood no longer being associated with psychological distress. Conclusions While single employed mothers did experience higher levels of psychological distress than their partnered counterparts, differences between these groups of women in income adequacy, psychosocial work quality, and work-family conflict were found to explain this relationship. Future research employing a longitudinal design and subject to lower selection biases is required to tease out the interrelationship of these three life strains and to point to the most appropriate economic and social policies to support single mothers in the workforce.